Continuity of Traditions of Musical Art - Kamilovna, Sokolova Fotima (Research Parks Publishing LLC, 2023)
This article raises questions related to the study of the phenomenon of musical dynasties and families. The role and position of the dynasties that have made a great contribution to the development of world musical art with their prolific and numerous creative activities will be studied. Aspects such as the importance of the family environment, social continuity, hereditary inclinations and abilities, traditions in educating the young generation of artists, as well as the activities of musical dynasties and families known in the fields of Uzbek composer and performing arts are studied. directly considered.